Urban and Rural Families: A Comparative Study of the Impact of Stress on Family Interaction - David R. Imig (Journal of Research in Rural Education, 1983)
This longitudinal study investigated the differential impact of stress, as caused by accumulated life change events, on 101 rural and urban families. It was concluded that the "piling-up" of stressor events inversely influenced the intrafamilial relations for rural, but not urban, families-and most specifically for young rural families. Such conclusions may be interpretated as being supportive of both the traditional distinctions between urban and folk families, and the concept of agrarianism. Implications for the mental health and educational sectors of rural communities are discussed: